Associations between vitamin D levels and dietary patterns in patients with Hashimoto’s thyroiditis - Kaličanin, Dean; Cvek, Maja; Barić, Ana; Škrabić, Veselin; Punda, Ante; Boraska Perica, Vesna (Frontiers in Nutrition, 2023)
Introduction: Vitamin D insufficiency is a global health problem affecting healthy and diseased individuals, including patients with Hashimoto’s thyroiditis (HT). Identifying dietary factors that may affect vitamin D levels and providing dietary guidelines accordingly can alleviate this problem. We therefore aimed to identify still unknown associations of dietary patterns, assessed through the Food Frequency Questionnaire (FFQ) with vitamin D blood levels. Materials and methods: FFQ was collected from 461 patients from Croatian Biobank of Patients with Hashimoto’s thyroiditis (CROHT), while total 25(OH)D was measured from their stored serum samples. We performed linear regression analysis between vitamin D levels and weekly intake of 24 food groups in 461 patients with HT (ALL), and in two disease-severity groups (MILD and OVERT). Results: The main results of our study are observations of: 1) an inverse association between vitamin D levels and coffee consumption (ALL: β=-0,433, P=0,005; OVERT: β=-0,62, P=0,008); 2) an inverse association between vitamin D levels and sweets consumption (ALL: β=-0,195, P=0,034; OVERT: β=-0,431, P=0,006); 3) positive association between vitamin D levels and vegetable consumption (ALL: β=0,182, p=0.019; OVERT, β=0,311, P=0,009). Importantly, effect sizes of all three associations were more prominent in HT patients with prolonged and more severe disease (OVERT). Conclusions: Further research into the functional and causal relationships of the observed associations is important to provide guidance regarding coffee/sugar intake on vitamin D status. A well-balanced diet can help prevent vitamin D deficiency and improve the quality of life of patients with HT, especially those in later stages of disease characterized by greater metabolic imbalance.